Una doble infección viral en orquídeas del género Cymbidium - Velasco, Ana Cecilia (1986)
A double -viral infection in Cymbidium hybrids is described. Virions were discovered by negative staining of sick plant sap, which showed a rigid type and a flexible virus. Two types of viral-cytoplasmatic inclusions, corresponding to both viruses, were observed in the ultrafine cuts of injured foliar areas. In one cell two types of inclusions were found together. By ultracentrifugation in saecharose gradients, these two types of virions could not be completely separeted, probably due to their fragmentation and aggregation. The rigid virus was related to the orchid race of tobacco mosaic virus, the flexible to the cymbidium mosaic virus. They affect orchids by producing a clinical case, which includes chlorotic and necrotic striate mosaics.